2005
DOI: 10.1002/em.20117
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian cell mutagenesis of the DNA adducts of vinyl chloride and crotonaldehyde

Abstract: Vinyl chloride and crotonaldehyde are known mutagens and carcinogens that, through their reaction with DNA, form specific deoxyguanosine adducts. To investigate the mutagenic potential of a subset of the possible deoxyguanosine lesions, site-specific adducts of vinyl chloride and crotonaldehyde were synthesized, inserted into a shuttle vector, and replicated in mammalian cells. Mutation yields of the DNA adducts of vinyl chloride and crotonaldehyde were found to be 2% and 5-6%, respectively, thus suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 27 publications
0
46
0
3
Order By: Relevance
“…47 Our post-synthetic modification strategy 48 allowed preparation of various dG enal adducts from a single modified phosphoramidite. A challenge was the preparation of stereochemically-defined amino diols for the crotonaldehyde (31,32) and 4-HNE adducts (33)(34)(35)(36) (Figure 2). [49][50][51][52] This strategy could not be applied to oligodeoxynucleotides containing α-OH-PdG (10), which were prepared using the modified phosphoramidite 25.…”
Section: Synthesis Of Oligodeoxynucleotides Containing 1n 2 -Dg Enalmentioning
confidence: 99%
“…47 Our post-synthetic modification strategy 48 allowed preparation of various dG enal adducts from a single modified phosphoramidite. A challenge was the preparation of stereochemically-defined amino diols for the crotonaldehyde (31,32) and 4-HNE adducts (33)(34)(35)(36) (Figure 2). [49][50][51][52] This strategy could not be applied to oligodeoxynucleotides containing α-OH-PdG (10), which were prepared using the modified phosphoramidite 25.…”
Section: Synthesis Of Oligodeoxynucleotides Containing 1n 2 -Dg Enalmentioning
confidence: 99%
“…TLS across the monoadducts has been characterized in human cells (22) and simian kidney cells (29). The study with human cells (22) reported that the S monoadduct was more miscoding than was the R monoadduct (10% vs 5%).…”
Section: Translesion Events Across Authentic and Model Iclsmentioning
confidence: 99%
“…Soc. 125,[50][51][52][53][54][55][56][57][58][59][60][61]. Molecular dynamics calculations, restrained by NOE-based distances and empirical restraints, revealed that both the 5′-Cp-N 2 -dG-3′-R-(R)-CH 3 -propyl-5′-Cp-N 2 -dG-3′ and 5′-Cp-N 2 -dG-3′-S-(R)-CH 3 -propyl-5′-Cp-N 2 -dG-3′ cross-links were located in the minor groove and retained Watson-Crick hydrogen bonds at the tandem cross-linked C‚G base pairs.…”
mentioning
confidence: 99%